(untitled) (Acta Scientiarum. Biological Sciences, 2021)
Cyanobacterial blooms can cause severe ecological and health problems in drinking water reservoirs. To alleviate this problem, allelopathically active submerged macrophytes can be used to reduce cyanobacterial growth. Accordingly, this study aimed to evaluate the sensitivity of strains of the Microcystis aeruginosa complex isolated from reservoirs with the presence and absence of submerged macrophytes to the allelochemicals of Ceratophyllum demersum. A coexistence experiment was carried out between the submerged macrophyte C. demersum and four Microcystis strains, with two treatments for each strain, one in coexistence with the submerged macrophyte (7 g L-1) and control (in the absence of the macrophyte). Two strains of M. aeruginosa (BMIUFRPE-06 and BMIUFRPE-07) and two of M. panniformis (BMIUFRPE-08 and BMIUFRPE-09) were used, which were isolated from Cajueiro (with submerged macrophytes) and Tapacurá (without submerged macrophytes) reservoirs, respectively. The biomass of Microcystis strains from the reservoir without macrophytes (BMIUFRPE-08 and BMIUFRPE-09) was significantly inhibited in 96% (T-test: p < 0.01) and 74% (T-test: p< 0.05), when compared to the control, respectively, with lower values of growth rates (ANOVA: p < 0.05). The strains isolated from the reservoir with macrophytes (BMIUFRPE-06 and BMIUFRPE-07) showed a growth delay (biomass reductions of 44 and 58%, respectively) in the coexistence treatment but without significant difference from the control on the sixth day of the experiment (biomass - T-test: p > 0.05; growth rate - ANOVA: p > 0.05). These results suggest that strains isolated from environments with submerged macrophytes are less sensitive to allelochemicals of these plants, as these strains may be adapted to the coexistence with submerged macrophytes. Situs barbarslot terpercaya dengan berbagai pilihan permainan seru, peluang menang besar, dan fitur bonus menarik. Nikmati pengalaman bermain aman dan menyenangkan kapan saja! Barbarslot adalah salah satu situs resmi https://www.26barsandaband.com/videos/, 5rb dan depo 5k terbaru dengan beragam permainan terbaik tahun 2025. Nikmati pengalaman bermain https://www.carsoncityantiquemall.com/contact-3, grafis epik dan fitur bonus hadir untuk meningkatkan peluang kemenangan. Rasakan keseruan bermain di om88 dengan peluang menang yang lebih besar. Nikmati pengalaman bermain yang seru, aman, dan penuh tantangan. Segera coba dan raih kemenangan besarmu! Situs gacorqq adalah game yang sering memberikan kemenangan besar, meskipun hasilnya tetap acak, tak bisa diprediksi, dan bergantung pada keberuntungan pemain. Tempat terbaik hari ini untuk bermain game slot, dengan beragam permainan tersedia cukup dengan minimal deposit 5000 di situs gacorqq login, Anda dapat bermain sepuasnya dan kapan saja. Hadir untuk Anda slot deposit 5000, bersama situs gacor5000 raih kemenenangan mudah dan juga fasilitas game terlengkap beda dari lainnya. kumolojoyo https://pn-batang.go.id/id/ https://www.ppdkk.edu.my/ https://cyclinic.com.tw/ https://carriesbridalcollection.com/ https://inspimate.co.ke/ https://www.affluence-inf.com/ https://socialmovementtechnologies.org/ https://www.dac-hr.com/ https://ican4ir.com/ https://ucrnn.net/ https://family-life.co/ https://pelangideco.com/ https://elsekgroup.com/ https://icanleaduganda.com/ https://lowveldfruits.co.za/ https://dominionng.com/ https://www.lwuc.org/ https://acadasuite.com/ https://noraktech.com/ https://burocromatico.mx/ https://norakle.com/ https://downeyrootcanal.com/ https://www.summit-smile.com/ https://www.mycreativesmiles.com/ https://appetito.uz/ https://adsec.net/ https://fahariloungemalindi.com/ https://dahnanproperties.com/ https://foresthydrology.gov.bc.ca/ https://www.gebhardtforcolorado.com/ https://gitlab.weather.noaa.gov/ https://msoid.abom.org/ https://www.rogeebeverlyhills.com/ https://wasre-datamover.umaryland.edu/ https://worthyfigures.com/ https://www.helsingborgsakademin.helsingborg.se/ https://saa.uinsgd.ac.id/ https://designsbylillianj.com/ https://www.tsv-einheit.de/ https://starbuckspartnerhoursinfo.com/ https://infosphereeducation.com/ https://amandlaomnotho.com/ https://puntacanard.do/ https://alessandraquartaconte.com/ https://sieudaga.com/ https://horusservices.com.co/ https://tiffanyqueen.store/ https://accessstudentportal.com/ https://www.fitlifefoundations.com/ https://www.nukandy.com/ https://filipinofoodcart.com/ https://starbridgeguides.com/ https://3beansart.com/ https://www.iestpahtsihuas.edu.pe/ https://worldoffoods.net/ https://abejotaburnaby.cl/ https://peoplesopioidsummit.com/ https://voordeliggenieten.nl/ https://bewealthyandjoyful.com/ https://fabiananliker.com/ https://ipracticegolf.com/ https://lhbtiqontact.nl/ https://maxdiscountcodes.com/ https://stturtle.com/ https://clickcatalystai.com/ https://grubz.co.za/ https://ir-terrasverwarming.nl/ https://refael-group.co.il/ https://www.thedriftlesssheep.com/ https://yabolichina.com/ https://www.gr4nt.com/ https://moviestylepopcorn.com/ https://pcavisen.dk/ https://emersonart.com/ https://surfessay.com/ https://tuaton.com/ https://chelsea-westside.com/ https://jadejewlery.com/ https://sencesecret.com/ https://www.passticks.com/ https://detucasa.online/ https://davidrefael.co.il/ https://refaelgroup.co.il/ https://verygoodclean.com/ https://www.knightvisor.com/ https://klinkerhaus-am-wald.de/ https://medicata.ee/ https://refael-nadlan.co.il/ https://www.bajioffer.com/ https://buycyh.com/ https://giuseppemagra.com/ https://www.kutivzkouture.co.uk/ https://lenyvankessel.nl/ https://the-domains.com/ https://thenativeborne.com/ https://windowsandoors.co.uk/ https://max-aperture.com/ https://www.tacology101.com/ https://paragontelco.com/ https://dataleaked.com/ https://brassringlineage.co/ https://capelsoundhaven.com.au/ https://goldcoastmecfs.com/ https://sbtienda.com/ https://shehealth.com/ https://worldofteas.ca/ https://mamieexcels.com/ https://patriotluxpools.com/ https://cascadesculinary.com/ https://texasprideconcrete.com/ https://recipetohappy.com/ https://laalquiladora.com/ https://thevpsacademy.com/ https://ministry-websites.com/ https://businesswebsiteservices.net/ https://sqrealty.com.mx/ https://emrooznama.com/ https://hubbil.com/ https://seoactions.com/ https://testlang.com/ https://thevinenetwork.com/ https://yogaconmarcella.com/ https://lakehouseufaula.com/ https://elliotpro.com/ https://nftgallerycenter.com/ https://eastexhomecenter.com/ https://culturallyresponsiveminds.com/ https://leadgeeks.net/ https://nextwavestrategies.ai/ https://naju.us/ https://roofingmasters.ca/ https://smokemart.ca/ https://www.maquette.ca/ https://www.caraccidentattorneycolumbia.com/ https://www.ergotijm.nl/ https://www.earthyoga.store/ https://acesdrains.com/ https://agentedesegurosdesalud.com/ https://asportdesigns.com/ https://astatic-solutions.com/ https://beattiepropertyservices.com/ https://bigwestgiftsuite.com/ https://bleroofing.com/ https://bmugc.com/ https://cardsandcrime.com/ https://dharmasimple.com/ https://ebolightmd.com/ https://anovelidea.com.au/ https://calvaryhill-lyman.org/ https://eficon.cl/ https://divinorigen.cl/ https://einsparhelden.de/ https://bulkbuydirect.store/ https://www.caedenfetters.com/ https://www.duncandigital.com/ https://elixirclio.com/